ELUCIDATING THE GONADAL DEVELOPMENT AND SEX DIFFERENTIATION OF THE RICE PADDY EEL, Monopterus albus (Zuiew, 1993), BASED ON GONADAL HISTOMORPHOLOGY AND STEROID HORMONE LEVELS - Nisperos, Dulce Marie Pili; Ramos, Gliceria B. (Malaysian Journal of Science, 2021)
The establishment and survival of the population of species in their breeding ground can be attributed to the species’ reproductive characteristic and capacity. The Monopterus albus species is an introduced fish in the Philippines. It is a protogynous hermaphrodite which has a natural ability for sex reversal. This study describes the histomorphology of the different stages of gonadal maturation and determines the concentration levels of the steroid hormones 17ß-estradiol (E2) and testosterone (T) in the blood plasma. These aim to a further understanding on the gonadal development and sex differentiation of the rice paddy eel as a hermaphroditic fish. Fish samples were collected randomly from farm ponds located in three provinces within the island of Luzon, Philippines. The sexual identity of the fish was categorized based on the presence or absence of ovarian and testicular tissues. Histological analysis of the gonad showed that immature, maturing-matured female gonad exhibited ovarian tissues of varying stages. The intersex gonad showed the existence of both ovarian and testicular tissues. Enzyme-linked immunosorbent assay (ELISA) was used to determine the concentration levels of gonadal steroid hormones. Differences in the concentration levels of the two hormones were evident across all the stages of gonad maturation. The functional role of these hormones in vitellogenesis and spermatogenesis leads to the development of this sex-changing gonads. This reproductive characteristic contributes to our understanding of the reproductive success of hermaphroditic fish.